Granting Credit In Cooperatives Using Profile Matching Method - Hariani, Pipit Putri (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2021)
Cooperatives is an institution economic have function in the process of the increase in community welfare, Travel cooperatives not easy to reach position like now. The existence of movement cooperatives as an institution economic expected to act as propulsion engine national economic activity as well as soko teachers the country economy. Bhakti BPJS Kesehatan Service Cooperative is a cooperative engaged in services, forms of cooperative services to the community one is to lend funds (credit) to help resolve the financial problems in the community. In granting the credit cooperatives need to do proper research and calculations to prospective customers who will take credit cooperatives, to avoid mistakes in decision making required data processing is fast, precise and accurate. With the Application Profile Matching Method For Determining Eligibility Lending In BPJS Kesehatan Service Cooperative Bhakti is the best solution to solve the problems that exist in this company, because with this method the decision taken by the cooperative members have been more thorough and detailed than the previous.